2019
DOI: 10.3390/vaccines7030076
|View full text |Cite
|
Sign up to set email alerts
|

Nanoparticle Vaccines for Inducing HIV-1 Neutralizing Antibodies

Abstract: The enormous sequence diversity between human immunodeficiency virus type 1 (HIV-1) strains poses a major roadblock for generating a broadly protective vaccine. Many experimental HIV-1 vaccine efforts are therefore aimed at eliciting broadly neutralizing antibodies (bNAbs) that are capable of neutralizing the majority of circulating HIV-1 strains. The envelope glycoprotein (Env) trimer on the viral membrane is the sole target of bNAbs and the key component of vaccination approaches aimed at eliciting bNAbs. Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
56
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 42 publications
(62 citation statements)
references
References 95 publications
(154 reference statements)
3
56
0
Order By: Relevance
“…Because previous work involving icosahedral nanoparticle scaffolds displaying HIV-1 Env trimers has shown that antigen crowding can modulate the accessibility of specific epitopes and thereby influence the humoral immune response 19,36 , we characterized the antigenicity of the BG505 SOSIP fusion nanoparticles in more detail.…”
Section: Geometriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Because previous work involving icosahedral nanoparticle scaffolds displaying HIV-1 Env trimers has shown that antigen crowding can modulate the accessibility of specific epitopes and thereby influence the humoral immune response 19,36 , we characterized the antigenicity of the BG505 SOSIP fusion nanoparticles in more detail.…”
Section: Geometriesmentioning
confidence: 99%
“…These proteins represent a panel of molecules well-suited to probe not only the adaptive immune response, but also other biological systems across various size scales.The ability to fully customize the structures of nanoparticle scaffolds could be particularly useful for HIV-1 Env-based immunogens. While previous studies of nanoparticle-displayed HIV-1 Env trimers have demonstrated enhanced immunogenicity39 , the effects are often modest compared to those observed for other antigens1,2,18,36 . While there may exist intrinsic peculiarities to HIV-1 Env that limit increases in Ab responses upon multivalent display40,41 , limitations associated with epitope inaccessibility caused by crowding of the trimers on nanoparticle surfaces have also been identified19 .…”
mentioning
confidence: 98%
“…Multimerization of Env glycoproteins on viral-resembling particles has also been achieved by their fusion to bacterial self-assembling proteins, like ferritin from Helicobacter pylori, E2 protein from Geobacillus stearothermophilus and lumazine synthase from Aquifex aeolicus [200,201]. BG505.SOSIP antigens presented on ferritin nanoparticles induced stronger neutralizing responses than their soluble trimer counterparts in rabbits [202,203]. The autologous Tier 2 responses were not significantly increased, but the Tier 1A responses were, probably due to the presentation of linear V3 epitopes on nonnative Env forms on ferritin particles [202].…”
Section: Nanoparticle Presentationmentioning
confidence: 99%
“…The inability to control the quality of Env or of nanoparticles can be a drawback of the use of in vivo-assembling protein nanoparticles. However, this can be overcome by using twocomponent platforms where native-like, trimeric Env and nanoparticles are expressed and purified separately and then assembled in vitro (Brinkkemper and Sliepen, 2019).…”
Section: Discussionmentioning
confidence: 99%